THE EFFECTIVENESS OF USING WORDWALL MEDIA IN THE TEACHING READING TO THE SEVENTH GRADE STUDENTS OF SMP NEGERI 5 KLATEN IN THE ACADEMIC YEAR 2025/2026 - Julianah, Evi; Hersulastuti; Haryono, Purwo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to investigate the effectiveness of using Wordwall media in teaching reading comprehension of descriptive texts to seventh grade students of SMP Negeri 5 Klaten in the 2025/2026 academic year. This research employed a quantitative research method with a quasi-experimental design. The instrument used in this study was a test consisting of pre-test and post-test. The data were collected through pre-tests and post-tests and analyzed using descriptive statistics and an independent sample t-test with the assistance of SPSS.The findings showed that the students’ reading comprehension achievement before the implementation of Wordwall media was relatively low. After the treatment, students in the experimental class demonstrated better reading comprehension achievement. The mean score of the control class was 67.03, while the mean score of the experimental class reached 79.53. These results indicate that students who learned through Wordwall media achieved higher reading comprehension scores than those who learned through conventional teaching methods. Based on the findings, it can be concluded that Wordwall media was effective in improving students’ reading comprehension of descriptive texts. The use of Wordwall provided an interactive and technology-based learning environment that increased students’ motivation, participation, and engagement in the learning process.Top of FormBottom of Form